Rantai Pasok Produk Beras di Kecamatan Cibeber, Kabupaten Cianjur - Alexandro Ephannuel Saragih; Netti Tinaprilla; Amzul Rifin (School of Business, Bogor Agricultural University (SB-IPB), 2017)
Integration in supply chain is the key of marketing. The objectives of this research were to identify the rice supply chain in Cibeber District in Cianjur Regency, to analyze the technical efficiency and vertical integration in the rice supply chain. Although the amount of rice product sold in Cipinang market is only small, the Cipinang grading system remains as a reference for the members of the rice supply chain in Cianjur. There were 10 marketing channels of rice product in Cibeber. Overall, the technical efficiency value of all channels had good scores, and this could be influenced by the sharing information process. Only four out of ten channels that had the technical efficiency, and this was caused by the large number of institutions involved in these channels. There was a directional causality from the farmers of Cibeber, Cianjur to the collectors and retailers of Cianjur. This represents that farmers’ power was not weak in the rice supply chain. The government needs to consistently oversee the rice storage performed by the wholesalers, especially in Cipinang Market. The increasing rice price in the wholesalers or retails was not caused by the increasing rice price the farmer level, but it was caused by the wholesaler market power to influence the rice supply in the marketKeywords: rice, supply chain, technical efficiency, vertical integration